Alongside but separate: Sympatric baleen whales choose different habitat conditions in São Miguel, Azores. (June 2022) - González García, Laura; Pierce, Graham J.; Autret, Emmanuelle; Torres-Palenzuela, Jesús M.
Abstract: Fin whales and sei whales are two migratory baleen whale species sighted every year across the waters of the Azores. Improved understanding of the ecological niche and habitat requirements of these baleen whales is needed to identify persistent or predictable oceanographic events that may set the time of their migration, as well as local or ephemeral oceanographic features that may aggregate their prey in a particular area. In dynamic environments such as the open ocean, mesoscale and submesoscale features can become decisive to determine the distributions of highly mobile species such as baleen whales. In this study, we analyse the habitat preferences of fin whales and sei whales around São Miguel Island (Azores) using environmental variables at different temporal and spatial scales. For both species, model results showed a clear influence of variables linked with primary production and therefore, prey availability; as well as a noticeable preference for oceanographically dynamic areas which directly affect distribution and aggregation of prey. Those environmental choices may indicate different levels of foraging habitat use for both species. Differences were found between the species, highlighting preferences for colder waters in fin whales and areas with stronger sea surface temperature gradients in sei whales. Model results obtained for fin whales were similar with those previously published for blue whales, suggesting that both species make similar use of the waters around São Miguel, often foraging during the migration across these waters. Results for sei whale, however, emphasize dynamic variables, indicating that travelling may prevail over feeding behaviour during their migration by the Azores. Highlights: Fin whales and sei whales are sighted in sympatry every year in Azores. Fin whale models indicate preference for dynamic areas and colder waters. Sei whale habitat suitability increases with strong temperature gradients. Highly mobile species habitat is analysed at different spatio-temporal scales. Long-term opportunistic whale watching data provides valuable cetacean information.